1998
DOI: 10.1038/sj.bjp.0701702
|View full text |Cite
|
Sign up to set email alerts
|

Receptor mechanisms involved in the 5‐HT‐induced inotropic action in the rat isolated atrium

Abstract: 1 The e ects of 5-hydroxytryptamine (5-HT) in rat cardiac preparations were studied. 5-HT up to 10 mM failed to a ect contractility in papillary muscles. However, in electrically driven (1 Hz) left atria 5-HT exerted a positive inotropic e ect that started at 1 mM and attained its maximum at 10 mM (312+50% of predrug value, n=8). 2 5-HT 10 mM stimulated the content of inositol-1,4,5-trisphosphate but not of cyclic AMP in rat left atria. 3 Plasma and serum levels of 5-HT amounted to about 0.3 mM and 15 mM, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 37 publications
0
38
0
1
Order By: Relevance
“…Taken together, these data might explain, at least in part, why many transmitters and hormones coupling to the PIP 2 -PLC-IP 3 cascade exert comparatively large positive inotropic effects in the atrium but only small or no positive inotropic effects in the ventricle (e.g. angiotensin II [131] or 5-hydroxytryptamine [124]). IP 3 does not alter myofilament Ca 2+ responsiveness [48].…”
Section: Ip 3 Signaling In Atrial Myocytesmentioning
confidence: 91%
See 1 more Smart Citation
“…Taken together, these data might explain, at least in part, why many transmitters and hormones coupling to the PIP 2 -PLC-IP 3 cascade exert comparatively large positive inotropic effects in the atrium but only small or no positive inotropic effects in the ventricle (e.g. angiotensin II [131] or 5-hydroxytryptamine [124]). IP 3 does not alter myofilament Ca 2+ responsiveness [48].…”
Section: Ip 3 Signaling In Atrial Myocytesmentioning
confidence: 91%
“…The atrial myocardium expresses numerous receptors coupling to the PIP 2 -PLC-IP 3 cascade. Increased phosphoinositide breakdown and inositol phosphate generation in atrium is mediated by receptors for acetylcholine (muscarinic, M 1 and M 3 ), angiotensin II (AT 1 ), endothelin (ET A ), histamine (H 1 ), 5-hydroxytryptamine (5-HT 2 ), norepinephrine (α 1 ) and vasopressin in various species including cat, chick, guinea-pig, mouse, rat and human [10,[112][113][114][115][116][117][118][119][120][121][122][123][124][125]. Furthermore, expression of IP 3 Rs in atrial myocytes has been demonstrated at mRNA and protein levels in various organisms, including mouse, rabbit, rat and human [15,17,41,58].…”
Section: Ip 3 Signaling In Atrial Myocytesmentioning
confidence: 99%
“…6) The cardiac stimulatory effects of 5-HT in the heart 7) were similarly attributed to the 5-HT 2 receptors present in cardiomyocytes.…”
Section: )mentioning
confidence: 98%
“…6) The cardiac stimulatory effects of 5-HT in the heart 7) were similarly attributed to the 5-HT 2 receptors present in cardiomyocytes. 8) However, the role of 5-HT antagonists in myocardial ischemic cellular damage remains unclear.…”
mentioning
confidence: 98%
See 1 more Smart Citation